Design and implementation of multilevel non-isolated DC-DC converter for variable DC voltage source - Ali Ahmed Adam Ismail; A. Elnady (Institute of Advanced Engineering and Science, 2021)
In this paper, a non-isolated multi-level DC-DC (MLDC-DC) smooth buck converter with the LC filter is designed and analyzed. The presented topology can be used in low or medium voltage levels in several applications that use DC storage elements. The use of the proposed multilevel converter topology reduces the voltage stress across the power converter switching elements and facilitates the voltage rating of the switches. The designed LC filter for the multilevel converter is characterized by a small inductor size, which reduces the traditional bulky inductor used in the output of the traditional DC-DC converter. The reduction in the filter size is proportional to the number of the connected voltage sources, it works effectively to reduce ripple in the load currents, and it increases the voltage gain. The intensive analysis of the converter system and the experimental results show a stable operation of the proposed converter with precise output voltage.